Organizational Training And Leadership Of Mosque Youth In Kerinjing Village - Mukhlis Mukhlis; Bernadette Robiani; Taufiq Taufiq; Suhel Suhel; Nazeli Adnan; Zulkarnain Ishak; Sukanto Sukanto; Hamira Hamira (Faculty of Economics, Universitas Sriwijaya, 2021)
The current phenomenon of understanding of organization and leadership in mosque youth organizations is still relatively lacking and doesn’t really understand how to manage an organization effectively and efficiently so that organizational goals haven’t been achieved optimally. This dedication aims to provide motivation to the management of youth mosques in Kerinjing Village to be more optimal and effective in organizational management. The dedication was carried out by means of lectures, training, and simulations to the mosque youth administrators in Kerinjing Village. The material provided is in the form of materials related to issues of leadership, conflict management, organizational management, and trial techniques. Through this dedication activity, it is hoped that it can provide skills for the administrators of youth mosques in Kerinjing village in managing organizations, forming management structures, and generating leadership talents. The expected output from this dedication activity is in the form of a final report and an article in a dedication journal. The results of this dedication are also expected to be the basis for the government in making policies and programs related to youth issues in rural areas.